Performance assessment of tall building-integrated wind turbines for power generation. (1st March 2016) - Li, Q.S.; Shu, Z.R.; Chen, F.B.
Highlights: The viability of tall building-integrated wind turbine is examined. Wind tunnel test is conducted to estimate wind speed amplification effects. Seasonal and monthly wind power generation by the turbines are estimated. Abstract: In response to the gradual degradation of the natural environment, there is a growing interest to advance the development of sustainable buildings, in which renewable energy technologies are often incorporated to strategically minimize the carbon footprint of buildings. Pearl River Tower, a 71-storey tall building in Guangzhou, China, was designed to be the most energy efficient tall building in the world. In addition to a series of energy-efficient measures, the most eye-catching innovation in the design of Pearl River Tower is the deployment of four wind turbines installed in four openings in the tall building for power generation. This study aims to provide a performance assessment of these tall building-integrated wind turbines. At the first step, a 1:150 scaled wind tunnel testing is carried out to experimentally assess the wind speed amplification effects inside the four openings. Comparative analysis and discussions corresponding to four different cases are presented. At the second step, the results from the wind tunnel testing, in conjunction with the statistical analysis results of long-term meteorological wind data recorded in Guangzhou, are applied for the performance assessment of these wind turbines for power generation. The outcomes of this study are expected to provide useful information for architects and engineers involved in the design of sustainable tall buildings.